Improving Rural Livelihoods in North East Kenya: Evidence of Sharia Cooperatives Outreach (Asian Journal of Social Science Studies, 2021)
Sharia cooperatives (SACCO) are essential low-cost financing that helps underserved communities in Kenya through giving loans, savings, school fees, and considerable group lending. This research used both the structured questionnaires and Focus Group Discussion methods to investigate Sharia cooperatives providers and clients as the best means of financial inclusion to support the disadvantaged people in North-East Kenya (NEK) counties. Four dimensions of financing outreach including scope, cost, worth, and depth sharia cooperatives outreach have been studied. The results have shown Kenyans sharia cooperatives have not achieved a reasonable scope of outreach. This might be due to what is found in the study the lack of qualified sharia cooperatives staff and both financial and digital financial illiteracies of the clients. The clients were found to have low knowledge of their products and services, lack of using the internet and digital devices, and more than 80% of them undertaking transactions at the premises and preferred direct contact. Moreover, the results showed the investigated SACCO did not reach the optimal worth outreach Due to the increase in the number of underserved people and the high rate of poverty in the remote rural areas. The results also show SACCO in Kenya have achieved reasonable depth outreach since they are covered the underserved community members such as women, youth but need to exert still more efforts to reach the remote rural areas. Although the customers have seen the cost of sharia cooperative services is reasonable, the results showed the high cost of attracting new clients. That might be due to the unused of the targeted communities the new means of connections such as webmail, internet, and smart devices. Based on these results the study might recommend that these SACCO might need to implement effective training strategies to enhance clients and staff knowledge to improve financial and digital illiteracy to improve the scope, worth, and cost outreach dimensions. The results also show low depth outreach due to the poor basic infrastructures, lack of capital to adopt wireless finance to expand to remote areas. For this study might recommend more capital injection for SACCO to adopt digital financial technology. These results give good policy implication for the Islamic Development Institution (IsDB), Islamic financial institutions, investors, and other alike to help these sharia cooperatives through capital injection, financial awareness seminars, telecommunication companies, and building capacity programs to promote this low-cost financing for the most disadvantaged Muslim minority in Kenya.